Difference between revisions of "1958 AHSME Problems/Problem 23"

(Created page with "== Problem == If, in the expression <math> x^2 \minus{} 3</math>, <math> x</math> increases or decreases by a positive amount of <math> a</math>, the expression changes by an am...")
 
m (Problem)
Line 1: Line 1:
 
== Problem ==
 
== Problem ==
  
If, in the expression <math> x^2 \minus{} 3</math>, <math> x</math> increases or decreases by a positive amount of <math> a</math>, the expression changes by an amount:
+
If, in the expression <math> x^2 - 3</math>, <math> x</math> increases or decreases by a positive amount of <math> a</math>, the expression changes by an amount:
  
<math> \textbf{(A)}\ {\pm 2ax \plus{} a^2}\qquad  
+
<math> \textbf{(A)}\ {\pm 2ax + a^2}\qquad  
 
\textbf{(B)}\ {2ax \pm a^2}\qquad  
 
\textbf{(B)}\ {2ax \pm a^2}\qquad  
\textbf{(C)}\ {\pm a^2 \minus{} 3} \qquad  
+
\textbf{(C)}\ {\pm a^2 - 3} \qquad  
\textbf{(D)}\ {(x \plus{} a)^2 \minus{} 3}\qquad\\  
+
\textbf{(D)}\ {(x + a)^2 - 3}\qquad\\  
\textbf{(E)}\ {(x \minus{} a)^2 \minus{} 3}</math>
+
\textbf{(E)}\ {(x - a)^2 - 3}</math>
 
 
  
 
== Solution ==
 
== Solution ==

Revision as of 23:20, 13 March 2015

Problem

If, in the expression $x^2 - 3$, $x$ increases or decreases by a positive amount of $a$, the expression changes by an amount:

$\textbf{(A)}\ {\pm 2ax + a^2}\qquad  \textbf{(B)}\ {2ax \pm a^2}\qquad  \textbf{(C)}\ {\pm a^2 - 3} \qquad  \textbf{(D)}\ {(x + a)^2 - 3}\qquad\\  \textbf{(E)}\ {(x - a)^2 - 3}$

Solution

$\fbox{}$

See Also

1958 AHSC (ProblemsAnswer KeyResources)
Preceded by
Problem 22
Followed by
Problem 24
1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50
All AHSME Problems and Solutions

The problems on this page are copyrighted by the Mathematical Association of America's American Mathematics Competitions. AMC logo.png

Invalid username
Login to AoPS